Implementation of Digital Marketing in Increasing Customers at PT. Banua Mentor Pratama - Syafiqa; Ira Nuriya Santi; Syamsul Bachri; Anisah (PT. Global World Scientific, 2025)
This study focuses on the implementation of digital marketing carried out by PT Banua Mentor Pratama through the social media platforms WhatsApp Business, Instagram, and TikTok to increase the number of customers using private tutoring services. The results of the study show that although digital marketing has a positive effect on increasing the number of customers, the impact is not significant. However, companies that are active in digital marketing tend to experience an increase in the number of customers, which indicates a positive correlation between the level of online interaction and customer base growth. The increase in customers is more visible in the use of Instagram Ads and WhatsApp Business, while TikTok plays a greater role in expanding the market by increasing profile visits. This study suggests that although digital marketing provides good results, PT Banua Mentor needs to improve and enhance the quality of the content posted, and focus more on the distribution of educational content. Digital marketing opens up great opportunities for business development and needs to be maximized, considering the transformation from conventional marketing to digital which is very important in facing increasingly tight economic competition. To achieve more significant results, companies must develop more targeted strategies and utilize the features available on social media platforms more optimally.